Hydaticus (Prodaticus) hauthi sp. nov., a new diving beetle from the cloud forest in the Cordillera El Sira, Peru (Coleoptera: Dytiscidae) - Hendrich, Lars; Balke, Michael (Zootaxa, 2020)
A new species of the genus Hydaticus Leach, 1817, subgenus Prodaticus Sharp, 1882 (Coleoptera: Dytiscidae) has been discovered in the mountains of Cerros del Sira, Peru. It is here described as Hydaticus (Prodaticus) hauthi sp. nov.. It is morphologically similar to the Peruvian H. panguana Megna, Balke, Apenborn & Hendrich, 2019. The new species differs from H. panguana by its almost complete black dorsal surface and the shape of the median lobe. Diagnostic characters of both species, including illustrations of male genitalia and habitus, are presented, and a modified key for the 12 Neotropical species is provided.